Proposta de análise tecnopolítica das inovaç\~oes democráticas - Christiana Soares de Freitas; Rafael Cardoso Sampaio; Daniel Pitangueira de Avelino (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The goal of this article is to present a theoretical and methodological proposal for analyzing democratic innovations based on science and technology studies and the sociology of public action. The first dimension of the model focus on the initiatives' characteristics by identifying its political-institutional and sociotechnical aspects. The second dimension of analysis aims at identifying and assessing direct and formal implications of the innovations such as policy instruments. The third analytical dimension comprehends their indirect effects such as the strengthening of democracy. Though such implications are difficult to be measured, they are fundamental in shaping public actions. If these implications are not verified, democratic innovations tend to become resources to grant legitimacy to already established powers, leaving little space for effective democratic changes.
10419/284904
Keywords: D73; O35; N36; 330; democratic innovation; analysis model; technopolitics; social participation